Advanced Techniques in Filler Layering for the Malar Region: Implications for Cellular Integrity and Long-Term Outcomes - Soumitra Das; Mekkanti Manasa Rekha (International Journal of Biochemistry and Biomolecule Research, 2025)
Objective: This review investigates advanced filler layering techniques for the malar region, focusing on cellular integration, collagen remodeling, hydration dynamics via aquaporin channels, genetic responses, and filler performance over time. Emphasis is placed on high-density HA fillers (Lyft, Voluma, Volift, and Volux), examining cellular-level mechanisms, genetic interactions, and the role of key pathways (TGF-β, ERK/MAPK, AQP3) in long-term outcomes. Methods: A systematic review was conducted, focusing on genetic, cellular, and molecular research related to HA filler applications. We explore key mechanisms, genetic pathways, and potential adverse drug events (ADEs) at the cellular level, providing a foundation for safer and more effective filler applications. Results: Techniques that integrate filler layering with knowledge of cellular and genetic mechanisms enhance aesthetic longevity and minimize ADE risks. Genetic pathways like TGF-β and AQP3 contribute to filler integration, while variations in immune and inflammatory genes influence cellular responses and potential adverse reactions. Conclusion: Genetic insights can improve filler outcomes, reduce complications, and support the development of personalized filler approaches. Future research on hybrid fillers and genomic customization may further enhance these outcomes.
Keywords: AQP3; Genetic; Hyaluronic acid; TGF-β; cellular